Myocarditis Related to Sepsis in Young Male - -, Harrison; Irawaty, Agnita; J. Saputra, Ardian (PT. Kalbe Farma Tbk., 2016)
Sepsis is a complex disease and is the manifestation of the immune and inflammatory response to infection. Recent definitions recognize the importance of myocardial depression and include a low cardiac index (CI) or echocardiographic evidence of cardiac dysfunction as one of the diagnosis criteria of severe sepsis. We report a case of young male with septic shock, pneumonia, and acute myocarditis.